2015
DOI: 10.1149/2.0831602jes
|View full text |Cite
|
Sign up to set email alerts
|

Communication—Fabrication of a Uniformly Tin-Coated Three-Dimensional Copper Nanostructured Architecture by Electrodeposition

Abstract: A three-dimensional copper nanostructure architecture (3DC1) coated uniformly with a tin film was fabricated by electrodeposition. In these trials, a pyrophosphate bath was used for tin plating, and the effects of polyethylene glycol and formaldehyde additives on the morphology of the deposited tin were investigated. Relatively large tin particles were electrodeposited in an inhomogeneous manner over the 3DC1 surface when using a plating bath without additives. In contrast, 3DC1 coated with a uniformly thick t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…38 The specific surface area and other properties of the 3DC/CNT composite films will be examined in future work.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…38 The specific surface area and other properties of the 3DC/CNT composite films will be examined in future work.…”
Section: Resultsmentioning
confidence: 99%
“…The 3DC/CNT films fabricated in this study are expected to be used for various functional electrode applications, such as electrodes for electric double layer capacitors and lithium-ion batteries. 38 The specific surface area and other properties of the 3DC/CNT composite films will be examined in future work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For practical applications, a joining technology with a roughened plating film that does not rely on composite plating is desirable. We have already reported that a roughened electrodeposited copper film can be fabricated using a roughening agent [19], and that the roughened copper film acts as an effective current collector when applied to a lithium [20,21] or sodium [22] ion battery anode.…”
Section: Introductionmentioning
confidence: 99%